Tsukamoto Fuzzy Method Analysis in Laptop Damage Diagnosis (Retracted) - Laia, Yonata; Halim, Agusman (Journal of Computer Networks, Architecture and High Performance Computing, 2022)
The author's request letter for manuscript withdrawal is in the PDF download section. Dec 5, 2023